Carbon-coated iron-based catalyst as well as preparation method and application thereof
By using carbon coating and co-modification technology of alkali metal or nickel on iron-based catalysts, the problems of low temporal and spatial yield and poor stability in the process of CO2 hydrogenation to high-alcohols are solved, and high efficiency, stability and Low cost advanced alcohol preparation.
Patent Information
- Application Number
- CN202411521259.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
The existing iron-based catalysts have low temporal and spatial yields and poor stability in the process of hydrogenation of CO2 to produce advanced alcohols, making it difficult to achieve efficient continuous production.
Using carbon-coated alkali metal or alkali metal co-modified iron-based catalysts, the carbonization of iron trioxide into active iron species through alkali metal or its co-modification with nickel, improve CO2 conversion, and wrap it through carbon layer. The coating enhances the stability of the catalyst.
High-temporal and spatial yields were achieved, with CO2 conversion exceeding 30%, and high-temporal and spatial yields exceeding 300 g/kg/h, and the catalyst showed excellent use stability and low production costs.
Smart Images

Figure CN119386909A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an iron-based catalyst, and in particular to a carbon-coated iron-based catalyst and a preparation method and application thereof. Background Art
[0002] The information provided in this section is for the purpose of generally presenting the background of the present disclosure. To the extent described in this section, the work of the presently named inventors and aspects of the description that may not constitute prior art at the time of filing are neither explicitly nor implicitly admitted to be prior art to the present disclosure.
[0003] Higher alcohols are alcohols with a carbon number greater than 2 (abbreviated as C 2+ alcohol) C 2+ Alcohol has high energy density, safe transportation and good gasoline blending performance. It can be used as a fuel additive or directly as a clean fuel. 2+ Alcohols can be used as chemical intermediates or platform molecules to transform into downstream products, such as synthetic polymers, olefins, disinfectants, detergents, etc. Using CO2 as the carbon and oxygen source, C 2+ Alcohol, is a synthetic C 2+ The new green route to alcohol is expected to become a potential alternative (complementary) route to coal / petroleum or biofermentation routes. At the same time, due to the similar characteristics to the synthesis gas conversion reaction, the future CO2 catalytic hydrogenation process can be "directly" carried out on the synthesis gas conversion industrial device, which is convenient for industrial application.
[0004] Typical CO2 hydrogenation to C 2+ Catalyst systems for alcohols include precious metal systems (including Rh, Pt, Ir, Pd, etc.) and non-precious metal systems (including modified copper-based methanol synthesis catalysts, modified Fischer-Tropsch synthesis catalysts, and modified molybdenum-based catalysts). These catalyst systems still have problems such as low selectivity for higher alcohols (10-20%) and low space-time yield (<200 mg / g / h) (CN117983235A; CN116713030A; CN111185209B). In addition, although iron-based catalysts have also been reported to be used for CO2 hydrogenation to produce higher alcohols, they have problems such as poor stability and low space-time yield (CN116273016A). The reactors used for CO2 hydrogenation to produce higher alcohols mainly include tank reactors and fixed-bed reactors. Although tank reactors can obtain higher alcohols with high selectivity, a large amount of solvent needs to be added during the reaction process, and the product separation energy consumption is high, which is also not conducive to large-scale continuous production. Summary of the invention
[0005] The purpose of the present invention is to provide a carbon-coated iron-based catalyst and a preparation method and application thereof, which solves the problem of low space-time yield of existing iron-based catalysts. The prepared catalyst can be directly used to catalyze the hydrogenation of CO2 to produce higher alcohols, achieves a higher space-time yield of higher alcohols, and shows excellent stability in use.
[0006] In order to achieve the above object, the present invention provides a carbon-coated iron-based catalyst, which is carbon-coated iron oxide loaded with alkali metal or alkali metal and nickel; in the catalyst, the nickel loading is 0-3wt%, and the alkali metal loading is 0.5-5wt%.
[0007] Preferably, the alkali metal is selected from at least one of Li, Na, K, Rb and Cs.
[0008] More preferably, the alkali metal is selected from at least one of Na and K.
[0009] Preferably, the inner core of the catalyst is a Fe5C2 phase, the alkali metal or the alkali metal and nickel are distributed on the surface of the inner core, and a carbon layer is coated on the surface of the inner core.
[0010] The second object of the present invention is to provide a method for preparing the carbon-coated iron-based catalyst, which comprises: impregnating and modifying ferric oxide with an alkali metal salt, or impregnating and modifying ferric oxide with a nickel salt and an alkali metal salt in sequence, and then introducing an inert gas containing CO for reduction and carbonization treatment.
[0011] Preferably, nickel salt is used as a precursor, nickel is first introduced into ferric oxide by an impregnation method, and a nickel-modified ferric oxide catalyst is obtained after drying and calcining at 400°C for 6 hours; then, potassium salt is used as a precursor, potassium is introduced into the nickel-modified ferric oxide by an impregnation method, and then calcined at 350°C for 6 hours under flowing air conditions; or / and, the ferric oxide is prepared by ferric nitrate (Fe(NO3)3·9H2O) and ammonium carbonate precipitation method; or / and, in the inert gas containing CO, the concentration of CO in the inert gas is 10%.
[0012] Preferably, the method for preparing ferric oxide comprises: dripping an aqueous ammonium carbonate solution drop by drop into a ferric nitrate solution under stirring at 70°C, continuing stirring at 70°C, standing and aging at room temperature, and then filtering, washing, drying, and then calcining in a muffle furnace at 400°C.
[0013] More preferably, the volume ratio of the aqueous ammonium carbonate solution to the ferric nitrate solution is 1:1; the concentration of the aqueous ammonium carbonate solution is 0.37 mol / L; and the concentration of the ferric nitrate solution is 0.25 mol / L.
[0014] The third object of the present invention is to provide the use of the carbon-coated iron-based catalyst in the hydrogenation of CO2 to produce higher alcohols, wherein the higher alcohols are alcohols with a carbon number greater than 2.
[0015] Preferably, the application comprises: impregnating and modifying ferric oxide with an alkali metal salt, or impregnating and modifying ferric oxide with a nickel salt and an alkali metal salt in sequence, and then introducing an inert gas containing CO for reduction carbonization treatment; after the carbonization treatment is completed, cooling to a catalytic reaction temperature of 300 to 350°C, introducing a mixed gas of 3.0 MPa and 2000 to 8000 mL / g / h of CO2 and H2 as a reaction gas, and reacting to obtain higher alcohols.
[0016] More preferably, the catalytic reaction temperature is 320-350° C.; or / and the reaction space velocity of the mixed gas is 2000-4000 mL / g / h.
[0017] The carbon-coated iron-based catalyst of the present invention and its preparation method and application solve the problem of low space-time yield of existing iron-based catalysts and have the following advantages:
[0018] (1) The present invention adopts a novel carbon layer-coated alkali metal or alkali metal and nickel co-modified iron-based catalyst, which promotes the carbonization of ferric oxide into active iron species through alkali metal or alkali metal and nickel co-modification, thereby improving the CO2 conversion rate, and synthesizing higher alcohols in a fixed bed reactor with high space-time yield and high continuous synthesis, and has high activity (conversion rate>30%) and high target higher alcohol product space-time yield (>300g product / kg catalyst / h) for CO2 fixed bed continuous hydrogenation;
[0019] (2) The coating of the carbon layer and the co-modification of nickel and alkali metal elements in the present invention make the catalyst exhibit good reaction stability and good life stability;
[0020] (3) The iron-based catalyst used in the present invention is synthesized by a step-by-step impregnation method, which has a simple preparation process and is convenient for large-scale industrial production;
[0021] (4) The iron-based catalyst used in the present invention does not contain precious metals and is inexpensive, which is beneficial to reducing the production cost of higher alcohol products. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 HRTEM results (A) and high-angle annular dark field image (B) and element distribution of the carbon layer-coated nickel and potassium-modified iron-based catalyst prepared in Example 1 of the present invention; overlap in the figure: superposition of all element distributions; CK: carbon element distribution; FeL: iron element distribution; KL: potassium element distribution; Ni L: nickel element distribution; OK: oxygen element distribution.
[0023] Figure 2The stability test results of the carbon layer-coated nickel and potassium-modified iron-based catalyst in Example 6 of the present invention; the left ordinate is the selectivity of each product (excluding carbon monoxide), and the right ordinate is C 2+ Space-time yield of OH.
[0024] Figure 3 These are the stability test results of the potassium-modified iron-based catalyst coated with a carbon layer in Example 7 of the present invention.
[0025] Figure 4 HRTEM of the iron-based catalyst (without carbon layer coating) modified with nickel and potassium in Comparative Example 3 of the present invention.
[0026] Figure 5 The stability test results of the iron-based catalyst (without carbon layer coating) modified with nickel and potassium in Comparative Example 3 of the present invention.
[0027] Note: CH4 in the figure: methane; C 2+ 0 : Alkanes with carbon numbers greater than 2; C 2-4 = : an olefin having a carbon number of 2-4; C 5+ = : olefins with carbon number greater than 5; C1OH: methanol; C 2+ OH: alcohols with carbon numbers greater than 2; Others: other oxygen-containing compounds, including methyl acetate and acetone; STY of C 2+ Space-time yield of OH-higher alcohols. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] It should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.
[0030] In the present invention, all features defined in the form of numerical ranges or percentage ranges, such as values, quantities, contents and concentrations, are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0031] The features mentioned in the present invention can be combined arbitrarily, as long as there is no contradiction in the combination of these features, all possible combinations should be considered as the scope of this specification. Each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.
[0032] The present invention provides a carbon-coated iron-based catalyst, and the preparation method thereof comprises:
[0033] 1) Preparation of ferric oxide by ammonium carbonate precipitation
[0034] 100 mL of 0.37 mol / L ammonium carbonate aqueous solution was added dropwise into 100 mL of 0.25 mol / L ferric nitrate solution under stirring at 70°C, and stirring was continued at 70°C for 2 h. The solution was then aged at room temperature for 6 h. After filtering, washing, and drying, the solution was calcined in a muffle furnace at 400°C for 4 h to obtain ferric oxide.
[0035] 2) Preparation of carbon-coated alkali metal or alkali metal and nickel co-modified iron-based catalysts by step-by-step impregnation-carbonization method
[0036] Using nickel nitrate as a precursor, firstly, 0.5-3wt% of nickel was introduced into the above-mentioned ferric oxide by impregnation, and then, after drying and calcination at 400°C for 6h, a nickel-modified ferric oxide catalyst was obtained. Then, using potassium carbonate as a precursor, 0.5-5wt% of potassium was introduced into the nickel-modified ferric oxide by impregnation, and then, calcination was performed at 350°C for 6h under flowing air (50mL / min).
[0037] 3) The carbonization process is carried out in situ before the CO2 hydrogenation reaction to produce higher alcohols. The specific treatment conditions are: the material calcined at 350°C is treated for 5 hours at 10% (CO concentration in inert gas) CO / Ar (50 mL / min), GHSV (Gas Hour Space Velocity, i.e., the volume of gas flowing over each gram of catalyst per hour) = 20000 mL / g / h.
[0038] The carbon-coated iron-based catalyst provided by the present invention and its preparation method and application are described in detail below through Examples 1 to 7 and Comparative Examples 1 to 3.
[0039] Example 1
[0040] A carbon-coated iron-based catalyst, the preparation method of which comprises the following steps:
[0041] 1) Preparation of ferric oxide by ammonium carbonate precipitation
[0042] 100 mL of 0.37 mol / L ammonium carbonate aqueous solution was added dropwise into 100 mL of 0.25 mol / L ferric nitrate solution under stirring at 70°C, and stirring was continued at 70°C for 2 h. The solution was then aged at room temperature for 6 h. After filtering, washing, and drying, the solution was calcined in a muffle furnace at 400°C for 4 h to obtain ferric oxide.
[0043] 2) Preparation of carbon-coated alkali metal or alkali metal and nickel co-modified iron-based catalysts by step-by-step impregnation-carbonization method
[0044] Using nickel nitrate as a precursor, nickel was first introduced into the above-mentioned ferric oxide by an impregnation method, with a nickel loading of 0.5wt%, and then dried and calcined at 400°C for 6h to obtain a nickel-modified ferric oxide catalyst. Then, using potassium carbonate as a precursor, potassium was introduced into the nickel-modified ferric oxide by an impregnation method, with a potassium loading of 4wt%, and then calcined at 350°C for 6h under flowing air (50mL / min).
[0045] 3) Weigh 150 mg of nickel / potassium modified ferric oxide (with a nickel content of 0.5 wt% and a potassium content of 4 wt%) and load it into a Φ10 mm stainless steel tube reaction fixed bed. At 350° C., introduce 10% CO / Ar at a flow rate of 50 mL / min (normal pressure) for carbonization treatment (5 h).
[0046] After the carbonization treatment was completed, the temperature dropped to the catalytic reaction temperature of 320°C, and the reaction gas (24% CO2 + 72% H2) was introduced at 3.0MPa and a reaction space velocity of 8000mL / g / h (reaction gas flow rate of 20mL / min) for 15h. The reaction product was continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The results showed that the CO2 conversion rate was 30.2%, the higher alcohol selectivity was 17.5%, and the higher alcohol space-time yield was 245.9mg / g / h.
[0047] The high-resolution transmission electron microscopy and element distribution results of the carbon layer-coated nickel and alkali metal co-modified iron-based catalyst prepared in this example are shown in FIG. Figure 1 The results show that the surface of the prepared catalyst is covered with a carbon layer, the core is Fe5C2 phase, and Ni and K are distributed on the surface of the core.
[0048] Example 2
[0049] A carbon-coated iron-based catalyst is substantially the same as that in Example 1, except that the nickel content is 1.0 wt%.
[0050] The catalytic reaction was carried out under the same conditions as in Example 1. The product after the reaction was continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The CO2 conversion rate was 34.7%, the higher alcohol selectivity was 19.8%, and the higher alcohol space-time yield was 317.0 mg / g / h.
[0051] Example 3
[0052] A carbon-coated iron-based catalyst is substantially the same as that in Example 1, except that the nickel content is 3.0 wt%.
[0053] The catalytic reaction was carried out under the same conditions as in Example 2. The product after the reaction was continuously detected by gas chromatography, and no catalyst deactivation was found during the reaction. The CO2 conversion rate was 36.6%, the higher alcohol selectivity was 17.8%, and the higher alcohol space-time yield was 316 mg / g / h.
[0054] Example 4
[0055] A carbon-coated iron-based catalyst, the same as that in Example 2.
[0056] The catalytic reaction was carried out under substantially the same conditions as in Example 2, except that the reaction space velocity was 2000 mL / g / h (reaction gas flow rate 5 mL / min). The product after the reaction was continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The CO2 conversion rate was 40.1%, the higher alcohol selectivity was 15.6%, and the higher alcohol space-time yield was 246.0 mg / g / h.
[0057] Example 5
[0058] A carbon-coated iron-based catalyst, the same as that in Example 2.
[0059] The catalytic reaction was carried out under substantially the same conditions as in Example 2, except that the reaction space velocity was 4000 mL / g / h (reaction gas flow rate was 10 mL / min). The product after the reaction was continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The CO2 conversion rate was 36.3%, the higher alcohol selectivity was 17.8%, and the higher alcohol space-time yield was 262.0 mg / g / h.
[0060] Example 6
[0061] A carbon-coated iron-based catalyst, the same as that in Example 2.
[0062] The catalytic reaction was carried out under the same conditions as in Example 2, except that the reaction time was 300 h. The product after the reaction was continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The experimental results are as follows: Figure 2The CO2 conversion rate was maintained at 32.5%, the higher alcohol selectivity was maintained at 19.8%, and the higher alcohol space-time yield was maintained at 317.0 mg / g / h.
[0063] Example 7
[0064] A carbon-coated iron-based catalyst is basically the same as Example 6, except that: instead of impregnation with nickel salt, potassium-modified ferric oxide is used for carbonization treatment, and the potassium content is 4.0wt%.
[0065] The catalytic reaction was carried out under the same conditions as in Example 6. The products after the reaction were continuously detected by online gas chromatography. The space-time yield of higher alcohols was stable at 187 mg / g / h within 140 h, and then gradually decreased to 120 mg / g / h after 300 h. The selectivity of higher alcohols was stable at 18% within 300 h (see Figure 3 ). Comparison of Example 6 and Example 7 fully illustrates the carbon layer coated potassium and nickel co-modified iron-based catalyst (see Figure 2 , Example 6) has higher operational stability than the carbon layer coated potassium modified iron-based catalyst.
[0066] Comparative Example 1
[0067] The method is basically the same as Example 1, except that the ferric oxide is carbonized instead of being impregnated with potassium and nickel salts.
[0068] 150 mg of ferric oxide material was weighed and placed in a Φ10 mm stainless steel tube reaction fixed bed. At 350° C., 10% CO / Ar was introduced at a flow rate of 50 mL / min (normal pressure) for carbonization treatment (5 h).
[0069] The catalytic reaction was carried out under the same conditions as in Example 1. The products after the reaction were continuously detected by gas chromatography, and no catalyst deactivation was found during the reaction. The CO2 conversion rate was 24.1%, the selectivity of higher alcohols was 1.1%, and the space-time yield of higher alcohols was 13.1 mg / g / h. Methane (selectivity was 38.7%), olefins (C2-C5, selectivity was 18.7%) and alkanes (C2-C5, selectivity was 18.6%) were generated during the reaction, and the other by-product was CO, with a selectivity of 14.9%.
[0070] Comparative Example 2
[0071] The method is basically the same as Example 2, except that: instead of potassium impregnation, nickel-modified ferric oxide is used for carbonization treatment, and the nickel content is 1.0 wt%.
[0072] The catalytic reaction was carried out under the same conditions as in Example 2. The products after the reaction were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The CO2 conversion rate was 19.1%, the selectivity of higher alcohols was 0%, and the space-time yield of higher alcohols was 0 mg / g / h. Methane (selectivity was 56.6%), olefins (C2-C5, selectivity was 0.3%) and alkanes (C2-C5, selectivity was 18.2%) were generated during the reaction, and the other by-product was CO, with a selectivity of 18.9%.
[0073] Comparative Example 3
[0074] An iron-based catalyst (whose nickel content is 0.5wt% and potassium content is 4wt%), which is basically the same as Example 1, except that: in step 3), the catalyst is treated at 350°C in a pure H2 atmosphere (30mL / min) for 10h to obtain a potassium and nickel co-modified iron-based catalyst without a carbon layer coating, such as Figure 4 shown.
[0075] The catalytic reaction was carried out under the same conditions as in Example 6, except that the reaction was carried out at 320°C, 3.0 MPa, and 20 mL / min of reaction gas (24% CO2 + 72% H2) for 5 h, and then the reaction was continued under the same conditions for 150 h. The product after the reaction was continuously detected by online gas chromatography. The experimental results are shown in FIG. Figure 5 The space-time yield of higher alcohols was stable at 160 mg / g / h within 50 h, and then gradually decreased to 115 mg / g / h after 125 h. The selectivity of higher alcohols was stable at 18% within 50 h, and then gradually decreased to 16.8% after 125 h. Comparison of Example 6 with Comparative Example 3 fully demonstrates that the iron-based catalyst co-modified with potassium and nickel coated with carbon layer (see Figure 2 ) has higher stability in use than the iron-based catalyst modified with potassium and nickel without carbon layer coating.
[0076] Obviously, the iron-based catalyst co-modified with nickel, rare earth elements and alkali metals coated with a novel carbon layer in the present invention can catalyze the hydrogenation of CO2 into higher alcohols under milder reaction conditions, with high CO2 conversion rate, high space-time yield of target higher alcohols, and excellent stability in use. Compared with the results reported in the literature, the invented novel iron-based catalyst shows a higher space-time yield, and the present invention can be used for the upgraded utilization of waste CO2 in power plants, coal chemical industry and other fields, and has good application prospects.
[0077] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A carbon-coated iron-based catalyst, characterized in that: The catalyst is carbon-coated iron oxide loaded with alkali metal or alkali metal and nickel; In the catalyst, the nickel loading is 0-3wt%, and the alkali metal loading is 0.5-5wt%.
2. The carbon-coated iron-based catalyst according to claim 1, characterized in that The alkali metal is selected from at least one of Li, Na, K, Rb and Cs.
3. The carbon-coated iron-based catalyst according to claim 1, characterized in that The inner core of the catalyst is a Fe5C2 phase, the alkali metal or the alkali metal and nickel are distributed on the surface of the inner core, and a carbon layer is coated on the surface of the inner core.
4. The method for preparing a carbon-coated iron-based catalyst according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The ferric oxide is impregnated and modified by an alkali metal salt, or the ferric oxide is impregnated and modified by a nickel salt and an alkali metal salt in sequence, and then an inert gas containing CO is introduced for reduction and carbonization treatment.
5. The preparation method according to claim 4, characterized in that: Using nickel salt as a precursor, nickel was first introduced into ferric oxide by an impregnation method, and then the nickel-modified ferric oxide catalyst was obtained after drying and calcining at 400°C for 6 hours. Then, using potassium salt as a precursor, potassium was introduced into the nickel-modified ferric oxide by an impregnation method, and then calcined at 350°C for 6 hours under flowing air conditions. Or / and, the ferric oxide is prepared by precipitation method of ferric nitrate and ammonium carbonate; Or / and, in the inert gas containing CO, the concentration of CO in the inert gas is 10%.
6. The preparation method according to claim 5, characterized in that: The method for preparing ferric oxide comprises: The ammonium carbonate aqueous solution was added drop by drop into the ferric nitrate solution under stirring at 70°C, and stirring was continued at 70°C. The solution was allowed to stand for aging at room temperature, and then filtered, washed, dried, and calcined in a muffle furnace at 400°C.
7. The preparation method according to claim 6, characterized in that: The volume ratio of the aqueous ammonium carbonate solution to the ferric nitrate solution is 1:1; The concentration of the ammonium carbonate aqueous solution is 0.37 mol / L; the concentration of the ferric nitrate solution is 0.25 mol / L.
8. Use of the carbon-coated iron-based catalyst according to any one of claims 1 to 3 in the production of higher alcohols by hydrogenation of CO2, characterized in that: The higher alcohol is an alcohol having a carbon number greater than 2.
9. The application according to claim 8, comprising: The ferric oxide is impregnated and modified by an alkali metal salt, or the ferric oxide is impregnated and modified by a nickel salt and an alkali metal salt in sequence, and then an inert gas containing CO is introduced for reduction and carbonization treatment; After the carbonization treatment is completed, the temperature is lowered to the catalytic reaction temperature of 300-350° C., and a mixed gas of 3.0 MPa and 2000-8000 mL / g / h of CO2 and H2 is introduced as a reaction gas to obtain higher alcohols.
10. The use according to claim 9, wherein the catalytic reaction temperature is 320-350°C; or / and the reaction space velocity of the mixed gas is 2000-4000 mL / g / h.
Citation Information
Patent Citations
Preparation of molybdenum carbide-supported nickel-based catalysts and their application in the hydrogenation of carbon dioxide to ethanol
CN111185209B
CuFeIn catalyst for preparing low-carbon alcohol through carbon dioxide hydrogenation as well as preparation method and application of CuFeIn catalyst
CN116273016A
Molecular sieve catalyst for preparing low-carbon alcohol through selective hydrogenation of carbon dioxide as well as preparation method and application of molecular sieve catalyst
CN116713030A
Hydrogenation catalyst and preparation method thereof, and method for preparing low-carbon alcohol through carbon dioxide hydrogenation
CN117983235A